Catalyst for ammonia dehydrogenation, method for producing same, and method for producing hydrogen using same
By impregnating alkali metals and ruthenium in zeolites, a high-activity and low-cost ammonia dehydrogenation catalyst was prepared, which solved the problems of existing catalysts being deactivated at high temperatures and high Ru content, and achieved the effect of efficient and economical preparation of hydrogen from ammonia.
Patent Information
- Application Number
- CN202380066078.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-28
- Filing Date
- 2023-09-15
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ammonia dehydrogenation catalysts have problems of high temperature inactivation and high Ru content, and it is difficult to efficiently and economically prepare hydrogen from ammonia.
The catalyst for ammonia dehydrogenation is prepared by using zeolites containing intracrystal cations to impregnate alkali metals and ruthenium through specific impregnation amounts and process steps to reduce the Ru content and improve the activity of the catalyst.
An ammonia dehydrogenation catalyst that maintains high activity at low temperatures is achieved, reducing the production cost of the catalyst, and improving the ammonia conversion rate and hydrogen preparation efficiency.
Smart Images

Figure BDA0005310954670000071 
Figure BDA0005310954670000141 
Figure BDA0005310954670000151
Abstract
Description
Technical Field
[0001] The present invention discloses a catalyst for ammonia dehydrogenation, a preparation method thereof and a method for producing hydrogen using the catalyst. More specifically, the present invention discloses a catalyst for ammonia dehydrogenation capable of producing hydrogen from ammonia with high yield, a preparation method thereof and a method for producing hydrogen using the catalyst. Background Art
[0002] Recently, there has been growing global interest in the production and utilization of hydrogen energy (blue hydrogen and green hydrogen) as a sustainable and environmentally friendly alternative energy source that does not emit carbon dioxide.
[0003] Hydrogen energy production methods include green hydrogen produced by water electrolysis and pink hydrogen produced by nuclear energy. In particular, ammonia can be used not only as a carrier for hydrogen, but also as an energy source itself. In addition, when using an appropriate catalyst, ammonia can be dehydrogenated to produce hydrogen.
[0004] When hydrogen is produced from ammonia by the above method, the fields that can be applied are as follows. First, oil refining companies such as Hyundai Oilbank plan to renovate and improve existing gas stations that provide gasoline, diesel and liquefied petroleum gas (LPG) to create future gas stations (complex energy stations) that provide transportation fuels and all types of energy including gasoline, diesel, liquefied petroleum gas, hydrogen and charging in one stop. In particular, if the "hydrogen-powered car using fuel cells" being developed by Hyundai Motor and others is commercialized, oil refining companies are expected to supply hydrogen to the above-mentioned future gas stations, so hydrogen produced from ammonia is expected to be supplied to gas stations and used as a raw material for fuel cells. In addition, the oil refining and petrochemical industries require a large amount of hydrogen when producing various products, and as this hydrogen, if environmentally friendly hydrogen generated by the ammonia dehydrogenation process and not emitting carbon dioxide is used instead of hydrogen produced by existing processes that emit a large amount of carbon dioxide, such as natural gas reforming reactions such as steam methane reforming, it is expected to achieve the effect of reducing carbon dioxide emissions. In addition, it is also possible to consider using the hydrogen produced by the ammonia dehydrogenation reaction for power generation purposes. Ammonia itself is used as a raw material for power generation. It can produce energy without emitting carbon dioxide after combustion. However, ammonia has disadvantages due to its own characteristics, such as low calorific value and difficulty in ignition. In order to solve these problems, it is proposed to convert only part of the ammonia into hydrogen, and then generate electricity by co-combustion of ammonia and hydrogen to produce energy, or convert all the ammonia into hydrogen, and then generate electricity by burning hydrogen to produce energy. In this case, it is believed that the advantages of hydrogen such as high calorific value and easy ignition can be used to produce energy in an environmentally friendly way. Moreover, ammonia can not only produce energy by co-combustion or combustion with hydrogen, but also by converting ammonia into hydrogen and using the hydrogen produced in this way for fuel cells to produce energy in an environmentally friendly way. In more detail, it is believed that only part or all of the ammonia can be converted into hydrogen according to the target power generation, and then the hydrogen produced in this way can be used as a raw material for fuel cells to produce energy corresponding to the required power generation. Another use scheme of ammonia is that it can be used as a fuel for ships. Similar to the previous case of power generation, in the case of ships, ammonia can also be used as a fuel to produce energy for driving the ship. Therefore, when only a part of the ammonia or all of the ammonia is converted into hydrogen, it is considered possible to produce energy by co-combustion of ammonia and hydrogen, combustion of hydrogen, or linkage with additional fuel cells to drive the ship.
[0005] Therefore, there is increasing interest in the technology of producing hydrogen by dehydrogenation of ammonia worldwide, and it is judged that if a high-performance ammonia dehydrogenation catalyst is developed, it is expected to produce hydrogen by this catalyst and use the hydrogen produced in this way for various purposes.
[0006] Ruthenium (Ru)-based catalysts, which are usually used to manufacture highly active ammonia dehydrogenation catalysts, are expensive. In addition, when the ammonia dehydrogenation reaction temperature is high, there is a problem of accelerated catalyst deactivation. Therefore, it is very important to develop a catalyst that minimizes the Ru content and has high activity even at low temperatures. Therefore, there is a worldwide demand for the development of such a catalyst. Summary of the invention
[0007] Technical issues
[0008] One embodiment of the present invention provides an ammonia dehydrogenation catalyst capable of producing hydrogen from ammonia with high yield.
[0009] Another embodiment of the present invention provides a method for preparing a catalyst for ammonia dehydrogenation.
[0010] Yet another embodiment of the present invention provides a method for producing hydrogen from ammonia using a catalyst for dehydrogenation of ammonia.
[0011] Technical Solution
[0012] One aspect of the present invention provides a catalyst for dehydrogenation of ammonia, comprising:
[0013] Zeolites containing intracrystalline cations; and
[0014] Alkali metal and ruthenium impregnated in the zeolite.
[0015] The intracrystalline cations may include hydrogen ions (H + ), sodium ion (Na + ), potassium ion (K + ), calcium ions (Ca 2+ ), magnesium ion (Mg 2+ ), rubidium ion (Rb + ), cesium ion (Cs + ) or a combination thereof.
[0016] The impregnation amount of the alkali metal in the catalyst for ammonia dehydrogenation may be 5 parts by weight to 50 parts by weight relative to 100 parts by weight of the zeolite.
[0017] The alkali metal may include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), or a combination thereof.
[0018] The impregnation amount of the ruthenium in the catalyst for ammonia dehydrogenation may be 0.5 parts by weight to 10 parts by weight relative to 100 parts by weight of the zeolite.
[0019] The impregnation amount of the ruthenium in the catalyst for ammonia dehydrogenation may be 1 to 10 parts by weight relative to 100 parts by weight of the zeolite.
[0020] The Si / Al atomic ratio of the zeolite may be 1-30.
[0021] The BET specific surface area of the zeolite may be 300 to 900 m 2 / g.
[0022] The catalyst for ammonia dehydrogenation may further include an alkaline earth metal, a lanthanide metal, or a combination thereof impregnated in the zeolite.
[0023] The total impregnation amount of the alkali metal, the alkaline earth metal, and the lanthanide metal may be greater than 5 parts by weight and less than or equal to 50 parts by weight relative to 100 parts by weight of the zeolite.
[0024] The zeolite may include X-type zeolite, Y-type zeolite, USY-type zeolite, ZSM-5, β-type zeolite, chabazite, SAPO series zeolites, mordenite, L-type zeolite, A-type zeolite, RFCC spent catalyst, or a combination thereof.
[0025] Another aspect of the present invention provides a method for preparing a catalyst for ammonia dehydrogenation, comprising:
[0026] A step (S10) of providing a zeolite containing intracrystalline cations;
[0027] A step (S20) of impregnating the zeolite with an alkali metal;
[0028] A step of drying the zeolite impregnated with an alkali metal (S30);
[0029] a step (S40) of impregnating the dried zeolite with ruthenium; and
[0030] a step of drying the zeolite impregnated with the alkali metal and ruthenium (S50).
[0031] The method for preparing the catalyst for ammonia dehydrogenation may further include, after the step (S50), a step (S60) of contacting the dried zeolite with a reducing agent for activation.
[0032] The reducing agent may include hydrogen, ammonia, or a combination thereof.
[0033] Another aspect of the present invention provides a method for preparing hydrogen, comprising:
[0034] A step (S100) of bringing ammonia into contact with the ammonia dehydrogenation catalyst to generate hydrogen.
[0035] The step (S100) may be performed at a temperature of 300°C to 700°C.
[0036] The step (S100) can be performed at 500 hours -1 Up to 25,000hr -1 The operation is performed at a gas hourly space velocity of .
[0037] Effects of the Invention
[0038] The catalyst for dehydrogenation of ammonia according to one embodiment of the present invention can produce hydrogen from ammonia with a high yield. DETAILED DESCRIPTION
[0039] The ammonia dehydrogenation catalyst according to one embodiment of the present invention is described in detail below.
[0040] In this specification, the term "intracrystalline cation" refers to a cation that is present in the (Si,Al)O4 tetrahedron as a structural unit of zeolite to compensate for the Si 4+ Partially Al 3+ The cations existing in the zeolite crystal structure due to charge deficiency generated during the substitution can be easily substituted with other surrounding cations by ion exchange.
[0041] In this specification, the term "ion exchange method" refers to a method for exchanging the intracrystalline cations present in the zeolite crystal structure for cations such as Cs + Generally speaking, the ion exchange method is performed in the following manner, that is, after a substance containing the desired cation is prepared into an aqueous solution, zeolite is added to the prepared aqueous solution to obtain a slurry, and then stirred under the temperature, pressure and time conditions desired by the user. After sufficient stirring, the slurry containing the zeolite is filtered to obtain only the solid, which is further washed and dried. At this time, due to the characteristics of zeolite, only cations are exchanged, so the anions that once existed in the corresponding substance are removed together with the solution during the process of filtering the solution. Ion exchange is carried out along with Si 4+ Replaced by Al 3+ The reaction that occurs and the amount of ion exchange that can be achieved can theoretically correspond to the number of moles of Al present in the zeolite. However, in practice, depending on the size and charge of the cations to be exchanged, the amount of ion exchange performed is much less than the theoretical value.
[0042] In addition, in this specification, the so-called "impregnation method" is a method generally used when an active metal or a promoter is impregnated in a carrier, which means a method in which a solution having a volume equivalent to the pore volume of the carrier is added dropwise to the carrier and the active metal or promoter is loaded on the carrier surface. Specifically, a substance containing the metal required by the user is dissolved in a solvent that can dissolve the corresponding substance to prepare a solution, and the amount of the solution may be greater than the pore volume according to the solubility of the substance. When the catalyst is prepared by this method, unlike the ion exchange method, the required amount of metal can be easily impregnated in the carrier. However, unlike the ion exchange method, this method is to impregnate all substances in the carrier, rather than only selectively impregnating cations. Therefore, it will be necessary to remove unwanted anions by additional post-treatment methods such as heat treatment.
[0043] In addition, in this specification, the so-called "conversion of ammonia" means a value calculated according to the following mathematical formula 1:
[0044] [Mathematical formula 1]
[0045] Ammonia conversion rate (%) = number of moles of ammonia reacted / number of moles of ammonia initially supplied×100.
[0046] In addition, in this specification, the so-called "RFCC spent catalyst" means spent catalyst from a residual fluid catalytic cracking unit.
[0047] In addition, in this specification, "BET (Brunauer-Emmett-Teller) specific surface area" is measured using an apparatus of model ASAP2460 manufactured by Micromeritics.
[0048] The intracrystalline cations exist in the zeolite crystal structure rather than on the zeolite surface, which is different from the ruthenium, alkali metal, alkaline earth metal and / or lanthanide metal existing on the zeolite surface.
[0049] The intracrystalline cations may include hydrogen ions (H + ), sodium ion (Na + ), potassium ion (K + ), calcium ions (Ca 2+ ), magnesium ion (Mg 2+ ), rubidium ions (Rb + ), cesium ion (Cs + ) or a combination thereof.
[0050] The alkali metal is impregnated into the zeolite and exists not in the pores of the zeolite crystal structure but in the interior and / or on the surface of the zeolite, and is distinguished from the intracrystalline cations existing in the zeolite crystal structure.
[0051] The impregnation amount of the alkali metal may be 5 to 50 parts by weight relative to 100 parts by weight of the zeolite. If the impregnation amount of the alkali metal is within the above range, an ammonia dehydrogenation catalyst capable of improving ammonia conversion rate may be obtained.
[0052] Furthermore, the present inventors have confirmed through repeated experiments that the above-defined range of the impregnation amount of the alkali metal does not vary depending on the type of zeolite and the type and amount of cations in the crystal.
[0053] The alkali metal may include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), or a combination thereof.
[0054] The ruthenium (Ru), similar to the alkali metal, is impregnated in the zeolite and exists on the surface of the zeolite instead of inside the pores of the zeolite crystal structure, which is different from the intracrystalline cations existing in the zeolite crystal structure.
[0055] The impregnation amount of the ruthenium may be 0.5 to 10 parts by weight relative to 100 parts by weight of the zeolite. If the impregnation amount of the ruthenium is within the above range, an ammonia dehydrogenation catalyst capable of improving ammonia conversion rate may be obtained.
[0056] In addition, the limited range of the impregnation amount of ruthenium is similar to the limited range of the impregnation amount of the alkali metal, and does not vary depending on the type of zeolite and the type and amount of cations in the crystal. This is a fact confirmed by the inventors through repeated experiments.
[0057] Specifically, the impregnation amount of ruthenium may be 1 part by weight to 10 parts by weight relative to 100 parts by weight of the zeolite.
[0058] The Si / Al atomic ratio of the zeolite may be 1 to 30. If the Si / Al atomic ratio is within the above range, an ammonia dehydrogenation catalyst capable of improving ammonia conversion rate may be obtained.
[0059] Furthermore, the present inventors have confirmed through repeated experiments that the above-mentioned limited range of Si / Al atomic ratio does not vary depending on the type of zeolite and the type and number of cations in the crystal.
[0060] The BET specific surface area of the zeolite may be 300 to 900 m 2 If the BET specific surface area is within the above range, an ammonia dehydrogenation catalyst capable of improving ammonia conversion rate can be obtained.
[0061] Furthermore, the present inventors have confirmed through repeated experiments that the above-defined range of the BET specific surface area does not vary depending on the type of zeolite and the type and number of cations in the crystal.
[0062] In addition, the ammonia dehydrogenation catalyst may further include an alkaline earth metal, a lanthanide metal, or a combination thereof impregnated in the zeolite.
[0063] The total impregnation amount of the alkali metal, the alkaline earth metal and the lanthanide metal may be greater than 5 parts by weight and less than or equal to 50 parts by weight relative to 100 parts by weight of the zeolite. Specifically, when the catalyst for ammonia dehydrogenation also includes an alkaline earth metal, a lanthanide metal or a combination thereof impregnated in the zeolite, the total impregnation amount of the alkaline earth metal and the lanthanide metal may be arbitrarily adjusted within a range capable of achieving a target ammonia conversion rate. The so-called target ammonia conversion rate refers to the ammonia conversion rate that can be obtained under the conditions that the total impregnation amount of the alkaline earth metal and the lanthanide metal is "0" and the impregnation amount of the alkali metal is 5 to 50 parts by weight relative to 100 parts by weight of the zeolite.
[0064] The zeolite may include X-type zeolite, Y-type zeolite, USY-type zeolite, ZSM-5, beta-type zeolite, chabazite (e.g., SSZ-13), SAPO series zeolites (e.g., SAPO-5, SAPO-11, SAPO-34), mordenite, L-type zeolite, A-type zeolite, RFCC spent catalyst, or a combination thereof. However, the present invention is not limited thereto, and other types of zeolites may also be included within the scope of the present invention.
[0065] The following is a detailed description of a method for preparing a catalyst for ammonia dehydrogenation according to one embodiment of the present invention.
[0066] The method for preparing a catalyst for ammonia dehydrogenation according to one embodiment of the present invention comprises: providing a zeolite containing intracrystalline cations (S10), impregnating the zeolite with an alkali metal (S20); drying the zeolite impregnated with the alkali metal (S30); impregnating the dried zeolite with ruthenium (S40); and drying the zeolite impregnated with the alkali metal and ruthenium (S50).
[0067] Only when the step (S20) and the step (S30) are performed before the step (S40) and the step (S50) in time, the alkali metal and the ruthenium can be uniformly impregnated into the zeolite in the required amount. If the step (S40) and the step (S50) are performed before the step (S20) and the step (S30) in time, the alkali metal cannot be uniformly impregnated into the zeolite in the required amount.
[0068] In addition, the method for preparing the catalyst for ammonia dehydrogenation may further include, after the step (S50), a step (S60) of contacting the dried zeolite with a reducing agent for activation. The step (S60) may be performed in-situ in the same reactor as the step (S50).
[0069] The reducing agent may be a substance capable of reducing the ammonia dehydrogenation catalyst (particularly ruthenium).
[0070] For example, the reducing agent may include hydrogen, ammonia, or a combination thereof.
[0071] The following describes in detail a method for producing hydrogen according to an embodiment of the present invention using the catalyst for dehydrogenating ammonia.
[0072] The hydrogen production method according to one embodiment of the present invention may include a step of contacting ammonia with the above-mentioned ammonia dehydrogenation catalyst to generate hydrogen ( S100 ).
[0073] The step (S100) may be performed at a temperature of 300°C to 700°C.
[0074] In addition, the step (S100) can be performed at 500 hours. -1 Up to 25,000hr -1 The operation is performed at gas hourly space velocity (GHSV).
[0075] The present invention is described below by taking the following embodiments as examples, however, the present invention is not limited to the following embodiments.
[0076] Experimental Example 1: Cesium (Cs) impregnation based on the impregnation method
[0077] The incipient wetness impregnation method was used to impregnate cesium (Cs) into USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 625m 2 / g), and then dried at 80°C for 12 hours. The target impregnation amount and the actual impregnation amount (ICP analysis) of cesium (Cs) at this time are shown in Table 1 below.
[0078] Experimental Example 2: Cesium (Cs) replacement based on ion exchange method
[0079] The ion exchange method was carried out at 70°C for 20 hours to make the USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 625m 2 / g) of the hydrogen ions (H + ) is replaced by cesium ions (Cs + ) and then dried at 80° C. for 12 hours. The target substitution amount and actual substitution amount (ICP analysis) of cesium (Cs) at this time are shown in Table 1 below.
[0080]
[0081] Referring to Table 1 above, when based on the ion exchange method, the actual Cs replacement amount is not only much less than the target Cs replacement amount, but also even if the target Cs replacement amount increases, the increase in the actual Cs replacement amount will not exceed a certain limit value.
[0082] In contrast, referring to Table 1 above and Table 2 below together, when based on the impregnation method (ie, incipient wetness impregnation method), the actual Cs impregnation amount is not only similar to the target Cs impregnation amount, but also increases if the target Cs impregnation amount increases.
[0083] Example 1: Preparation of ammonia dehydrogenation catalyst
[0084] First, cesium (Cs) was impregnated as a promoter into USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 625m 2 / g), and then dried at 80°C for 12 hours. Then, ruthenium (Ru) was further impregnated into the USY type zeolite impregnated with cesium by the incipient wetness impregnation method, and then dried at 80°C for 12 hours. As a result, a catalyst for ammonia dehydrogenation in which 30 parts by weight of cesium (Cs) and 0.5 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite was obtained.
[0085] Example 2: Preparation of Catalyst for Ammonia Dehydrogenation
[0086] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the impregnation amount of ruthenium (Ru) was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 1.0 part by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0087] Example 3: Preparation of Catalyst for Ammonia Dehydrogenation
[0088] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the amount of ruthenium (Ru) impregnated was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0089] Example 4: Preparation of Catalyst for Ammonia Dehydrogenation
[0090] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the amount of ruthenium (Ru) impregnated was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 5.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0091] Example 5: Preparation of Catalyst for Ammonia Dehydrogenation
[0092] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the amount of ruthenium (Ru) impregnated was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 10.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0093] Example 6: Preparation of Catalyst for Ammonia Dehydrogenation
[0094] Except for changing the impregnation amount of cesium (Cs) and the impregnation amount of ruthenium (Ru), the catalyst for ammonia dehydrogenation was prepared by the same method as in Example 1. As a result, a catalyst for ammonia dehydrogenation in which 5.0 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite was obtained.
[0095] Example 7: Preparation of Catalyst for Ammonia Dehydrogenation
[0096] The catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the impregnation amount of cesium (Cs) and the impregnation amount of (Ru) were changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 50 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0097] Example 8: Preparation of Catalyst for Ammonia Dehydrogenation
[0098] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 1, BET specific surface area: 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0099] Example 9: Preparation of Catalyst for Ammonia Dehydrogenation
[0100] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 30, BET specific surface area: 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0101] Example 10: Preparation of Catalyst for Ammonia Dehydrogenation
[0102] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 300m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0103] Example 11: Preparation of Catalyst for Ammonia Dehydrogenation
[0104] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 900m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0105] Example 12: Preparation of Catalyst for Ammonia Dehydrogenation
[0106] In addition to using USY zeolite (Zeolyst, intracrystalline cation: Na +, Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0107] Example 13: Preparation of Catalyst for Ammonia Dehydrogenation
[0108] In addition to using USY zeolite (Zeolyst, intracrystalline cation: K + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0109] Example 14: Preparation of Catalyst for Ammonia Dehydrogenation
[0110] In addition to using USY zeolite (Zeolyst, intracrystalline cation: Ca 2+ , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0111] Example 15: Preparation of Catalyst for Ammonia Dehydrogenation
[0112] In addition to using USY zeolite (Zeolyst, intracrystalline cation: Mg 2+ , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H +, Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0113] Example 16: Preparation of Catalyst for Ammonia Dehydrogenation
[0114] In addition to using USY zeolite (Zeolyst, intracrystalline cation: Ru + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0115] Example 17: Preparation of Catalyst for Ammonia Dehydrogenation
[0116] In addition to using USY zeolite (Zeolyst, intracrystalline cation: Cs + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0117] Example 18: Preparation of Catalyst for Ammonia Dehydrogenation
[0118] In addition to using X-type zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0119] Example 19: Preparation of Catalyst for Ammonia Dehydrogenation
[0120] In addition to using Y-type zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0121] Example 20: Preparation of Catalyst for Ammonia Dehydrogenation
[0122] Except for ZSM-5 (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0123] Example 21: Preparation of Catalyst for Ammonia Dehydrogenation
[0124] In addition to using β-zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0125] Example 22: Preparation of Catalyst for Ammonia Dehydrogenation
[0126] In addition to using chabazite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0127] Example 23: Preparation of Catalyst for Ammonia Dehydrogenation
[0128] In addition to using SAPO series zeolites (Zeolyst, intracrystalline cations: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0129] Example 24: Preparation of Catalyst for Ammonia Dehydrogenation
[0130] In addition to using mordenite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0131] Example 25: Preparation of Catalyst for Ammonia Dehydrogenation
[0132] In addition to using L-type zeolite (Zeolyst, intracrystalline cation: H+ , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0133] Example 26: Preparation of Catalyst for Ammonia Dehydrogenation
[0134] In addition to using type A zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0135] Example 27: Preparation of Catalyst for Ammonia Dehydrogenation
[0136] In addition to using RFCC spent catalyst (HD Modern Oil Bank, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0137] Example 28: Preparation of Catalyst for Ammonia Dehydrogenation
[0138] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that lithium (Li) was used as a promoter instead of cesium (Cs). As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of lithium (Li) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0139] Example 29: Preparation of Catalyst for Ammonia Dehydrogenation
[0140] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that sodium (Na) was used as a promoter instead of cesium (Cs). As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of sodium (Na) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0141] Example 30: Preparation of Catalyst for Ammonia Dehydrogenation
[0142] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that potassium (K) was used as a promoter instead of cesium (Cs). As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of potassium (K) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0143] Example 31: Preparation of Catalyst for Ammonia Dehydrogenation
[0144] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that rubidium (Rb) was used as a promoter instead of cesium (Cs). As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of rubidium (Rb) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0145] Example 32: Preparation of Catalyst for Ammonia Dehydrogenation
[0146] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that francium (Fr) was used as a promoter instead of cesium (Cs). As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of francium (Fr) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0147] Comparative Example 1: Preparation of Catalyst for Ammonia Dehydrogenation
[0148] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the amount of ruthenium (Ru) impregnated was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 0.1 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0149] Comparative Example 2: Preparation of Catalyst for Ammonia Dehydrogenation
[0150] A catalyst for ammonia dehydrogenation was prepared in the same manner as in Example 1 except that the impregnation amount of ruthenium (Ru) was changed. As a result, a catalyst for ammonia dehydrogenation was obtained in which 30 parts by weight of cesium (Cs) and 15 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY zeolite.
[0151] Comparative Example 3: Preparation of Catalyst for Ammonia Dehydrogenation
[0152] Except for changing the impregnation amount of cesium (Cs) and the impregnation amount of ruthenium (Ru), the catalyst for ammonia dehydrogenation was prepared by the same method as in Example 1. As a result, a catalyst for ammonia dehydrogenation in which 0.3 parts by weight of cesium (Cs) and 2 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite was obtained.
[0153] Comparative Example 4: Preparation of Catalyst for Ammonia Dehydrogenation
[0154] Except for changing the impregnation amount of cesium (Cs) and the impregnation amount of ruthenium (Ru), the catalyst for ammonia dehydrogenation was prepared by the same method as in Example 1. As a result, a catalyst for ammonia dehydrogenation in which 0.5 parts by weight of cesium (Cs) and 2 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite was obtained.
[0155] Comparative Example 5: Preparation of Catalyst for Ammonia Dehydrogenation
[0156] Except for changing the impregnation amount of cesium (Cs) and the impregnation amount of ruthenium (Ru), the catalyst for ammonia dehydrogenation was prepared by the same method as in Example 1. As a result, a catalyst for ammonia dehydrogenation in which 60 parts by weight of cesium (Cs) and 2 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite was obtained.
[0157] Comparative Example 6: Preparation of Catalyst for Ammonia Dehydrogenation
[0158] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 0.5, BET specific surface area: 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0159] Comparative Example 7: Preparation of Catalyst for Ammonia Dehydrogenation
[0160] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 35, BET specific surface area: 625m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H +, Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0161] Comparative Example 8: Preparation of Catalyst for Ammonia Dehydrogenation
[0162] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 250m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0163] Comparative Example 9: Preparation of Catalyst for Ammonia Dehydrogenation
[0164] In addition to using USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area: 950m 2 / g) substituted USY zeolite (Zeolyst, intracrystalline cation: H + , Si / Al atomic ratio: 15, BET specific surface area 625m 2 / g), an ammonia dehydrogenation catalyst was prepared in the same manner as in Example 1. As a result, an ammonia dehydrogenation catalyst was obtained in which 30 parts by weight of cesium (Cs) and 2.0 parts by weight of ruthenium (Ru) were impregnated in 100 parts by weight of USY type zeolite.
[0165] Control Example 1: Preparation of catalyst for control group
[0166] First, an ion exchange method was performed at 70°C for 20 hours to make USY zeolite (Zeolyst, intracrystalline cations: H + ) + ) is replaced by cesium ions (Cs +), and then dried at 80°C for 12 hours. Then, ruthenium (Ru) was impregnated into the USY type zeolite in which the cesium ions were replaced by the incipient wetness impregnation method, and then dried at 80°C for 12 hours. As a result, a control catalyst was obtained in which 2.1 parts by weight of cesium (Cs) was replaced in 100 parts by weight of USY type zeolite and 2 parts by weight of ruthenium (Ru) was impregnated.
[0167] The components of the catalysts prepared in Examples 1 to 32, Comparative Examples 1 to 9 and Control Example 1 are sorted and shown in Table 2 below.
[0168]
[0169]
[0170] Evaluation Example 1: Ammonia Conversion Rate Evaluation
[0171] The catalysts prepared in Examples 1 to 32, Comparative Examples 1 to 9 and Control Example 1 were activated by in-situ hydrogen treatment. Then, the catalysts were heated at atmospheric pressure (1 atm), 450°C and a gas hourly space velocity of 12,000 hr. -1 Under the conditions of , 100% ammonia gas was brought into contact with each of the above catalysts, and the ammonia conversion rate was evaluated according to the mathematical formula 1. The results are shown in the following Table 3.
[0172]
[0173]
[0174] Referring to Table 3 above, it is shown that the ammonia conversion rates of the catalysts prepared in Examples 1 to 32 are higher than those of the catalysts prepared in Comparative Examples 1 to 9 and Control Example 1.
[0175] In addition, in the present specification, only cesium (Cs) was impregnated as an alkali metal to prepare the ammonia dehydrogenation catalyst, and the activity (i.e., ammonia conversion rate) of the ammonia dehydrogenation catalyst thus prepared was evaluated. However, since all alkali metals have substantially the same characteristics, when other alkali metals such as lithium (Li), sodium (Na), potassium (K), rubidium (Rb), francium (Fr) or a combination thereof are impregnated instead of cesium (Cs) to prepare the ammonia dehydrogenation catalyst, substantially the same results as the data recorded in Tables 2 and 3 above can be obtained, which is a matter of ordinary skill in the art.
[0176] The preferred embodiments of the present invention are described above with reference to the embodiments, but these are merely exemplary, and a person skilled in the art will appreciate that various modifications and equivalent embodiments can be realized. Therefore, the protection scope of the present invention should be determined according to the attached claims.
Claims
1. A catalyst for dehydrogenation of ammonia, comprising: Zeolites containing intracrystalline cations; and Alkali metal and ruthenium impregnated in the zeolite.
2. The catalyst for ammonia dehydrogenation according to claim 1, wherein The intracrystalline cations include hydrogen ions, sodium ions, potassium ions, calcium ions, magnesium ions, rubidium ions, cesium ions or combinations thereof.
3. The catalyst for ammonia dehydrogenation according to claim 1, wherein The impregnation amount of the alkali metal is 5 to 50 parts by weight relative to 100 parts by weight of the zeolite.
4. The catalyst for ammonia dehydrogenation according to claim 1, wherein The alkali metal includes lithium, sodium, potassium, rubidium, cesium, francium or a combination thereof.
5. The catalyst for ammonia dehydrogenation according to claim 1, wherein The impregnation amount of ruthenium is 0.5 parts by weight to 10 parts by weight relative to 100 parts by weight of the zeolite.
6. The catalyst for ammonia dehydrogenation according to claim 5, wherein The impregnation amount of the ruthenium is 1 to 10 parts by weight relative to 100 parts by weight of the zeolite.
7. The catalyst for ammonia dehydrogenation according to claim 1, wherein The Si / Al atomic ratio of the zeolite is 1-30.
8. The catalyst for ammonia dehydrogenation according to claim 1, wherein The BET specific surface area of the zeolite is 300 to 900 m 2 / g.
9. The catalyst for ammonia dehydrogenation according to claim 1, wherein The catalyst for ammonia dehydrogenation further includes an alkaline earth metal, a lanthanide metal or a combination thereof impregnated in the zeolite.
10. The catalyst for ammonia dehydrogenation according to claim 9, wherein The total impregnation amount of the alkali metal, the alkaline earth metal and the lanthanide metal is greater than 5 parts by weight and less than or equal to 50 parts by weight relative to 100 parts by weight of the zeolite.
11. The catalyst for ammonia dehydrogenation according to claim 1, wherein The zeolite includes X-type zeolite, Y-type zeolite, USY-type zeolite, ZSM-5, β-type zeolite, chabazite, SAPO series zeolite, mordenite, L-type zeolite, A-type zeolite, RFCC spent catalyst or a combination thereof.
12. A method for preparing a catalyst for ammonia dehydrogenation, comprising: Step S10 of providing a zeolite containing intracrystalline cations; Step S20 of impregnating the zeolite with an alkali metal; Step S30 of drying the zeolite impregnated with the alkali metal; Step S40 of impregnating the dried zeolite with ruthenium; and The step S50 of drying the zeolite impregnated with the alkali metal and ruthenium.
13. The method for preparing a catalyst for ammonia dehydrogenation according to claim 12, wherein: The method for preparing the catalyst for ammonia dehydrogenation further includes, after the step S50, a step S60 of contacting the dried zeolite with a reducing agent for activation.
14. The method for preparing a catalyst for ammonia dehydrogenation according to claim 13, wherein: The reducing agent includes hydrogen, ammonia or a combination thereof.
15. A method for producing hydrogen, comprising: A step S100 of bringing ammonia into contact with the ammonia dehydrogenation catalyst according to any one of claims 1 to 11 to generate hydrogen.
16. The method for producing hydrogen according to claim 15, wherein: The step S100 is performed at a temperature of 300° C. to 700° C.
17. The method for producing hydrogen according to claim 15, wherein: The step S100 is performed at 500 hours -1 Up to 25,000hr -1 The operation is performed at a gas hourly space velocity of .